Nuclear Import of Chromatin Remodeler Isw1 Is Mediated by Atypical Bipartite cNLS and Classical Import Pathway. (26th November 2012) - Vasicova, Pavla; Stradalova, Vendula; Halada, Petr; Hasek, Jiri; Malcova, Ivana
<x xml:space="preserve">Abstract</x> The protein Isw1 of Saccharomyces cerevisiae is an imitation‐switch chromatin‐remodeling factor. We studied the mechanisms of its nuclear import and found that the nuclear localization signal (NLS) mediating the transport of Isw1 into the nucleus is located at the end of the C‐terminus of the protein (aa1079–1105). We show that it is an atypical bipartite signal with an unconventional linker of 19 aa (KRIR X19 KKAK) and the only nuclear targeting signal within the Isw1 molecule. The efficiency of Isw1 nuclear import was found to be modulated by changes to the amino acid composition in the vicinity of the KRIR motif, but not by the linker length. Live‐cell imaging of various karyopherin mutants and in vitro binding assays of Isw1NLS to importin‐α revealed that the nuclear translocation of Isw1 is mediated by the classical import pathway. Analogous motifs to Isw1NLS are highly conserved in Isw1 homologues of other yeast species, and putative bipartite cNLS were identified in silico at the end of the C‐termini of imitation switch (ISWI) proteins from higher eukaryotes. We suggest that the C‐termini of the ISWI family proteins play an important role in their nuclear import.